BMS656: Functional Genomics / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2022)
This course surveys the basic findings and approaches in the field of genomics. The life sciences are being transformed by massive infusions of molecular sequence data together with new computational advances and database technologies. We will cover conceptual aspects as well as methodology and technical advances that are central to obtaining and exploring genome sequences. The course is design to equip student with new information on the latest technology in the genomic area. The topics covered are the basic knowledge on Next Generation Sequencing; determination of complete genome sequences and the exploitation of genome sequences to answer biological questions.